Nudging with care: The risks and benefits of social information - Cristina Bicchieri; Eugen Dimant (The University of Nottingham, Centre for Decision Research and Experimental Economics (CeDEx), 2019)
Norms and nudges are both popular types of interventions. Recent years have seen the rise of "norm-nudges" - nudges whose mechanism of action relies on social norms, eliciting or changing social expectations. Norm-nudges can be powerful interventions, but they can easily fail to be effective and can even backfire unless they are designed with care. We highlight important considerations when designing norm-nudges and discuss a general model of social behavior based on expectations and conditional preferences. We present the results of several experiments where norm-nudging can backfire, and ways to avoid these negative outcomes.
Keywords: B41; D01; D9; 330; Norm-Nudges; Nudge; Social Information; Social Norms